2006
DOI: 10.1161/01.str.0000244767.39962.f7
|View full text |Cite
|
Sign up to set email alerts
|

High von Willebrand Factor Levels Increase the Risk of First Ischemic Stroke

Abstract: Background and Purpose-Elevated von Willebrand factor (vWF) concentrations are associated with an increased risk of ischemic heart disease. Several factors influence vWF antigen levels and activity, including blood group, genetic variability, acute-phase response, and proteolysis by A Disintegrin and Metalloprotease with ThromboSpondin motif (ADAMTS13), a determinant of proteolytic cleavage of vWF. We assessed how these factors affect the relation between vWF and the occurrence of stroke to understand the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
177
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(191 citation statements)
references
References 25 publications
9
177
1
4
Order By: Relevance
“…This is in agreement with the study by Catto et al [7], which involved 169 patients with ischemic or hemorrhagic stroke. In contrast, significantly increased VWF levels at the 3-month follow-up were not detected in three other studies [5,6,17]. However, these studies only included a small number of patients at follow-up (26-64 patients) [5,6,17].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is in agreement with the study by Catto et al [7], which involved 169 patients with ischemic or hemorrhagic stroke. In contrast, significantly increased VWF levels at the 3-month follow-up were not detected in three other studies [5,6,17]. However, these studies only included a small number of patients at follow-up (26-64 patients) [5,6,17].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, blood sampling was standardized and performed at two time points, whereof one was in the chronic phase. Only a few previous studies [5][6][7]11,17] have examined VWF levels at more than one well-defined time-point. There are also some limitations that should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The association between ADAMTS13 and ischemic stroke has been investigated previously in small case-control studies. 10,[36][37][38] The association between low ADAMTS13 activity and ischemic stroke risk is likely to be explained by less cleavage of vWF HMWMs, which are the most prothrombotic. 4,35 Freynhofer et al affirm that vWF and its cleaving protease ADAMTS13 might play an important role in the development and perpetuation of vascular disease in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…9 Our results show that increased vWF levels, vWF activity, and modifications in the multimeric structure showing HMWMs all correlate with the incidence of stroke and could indicate a causal role of vWF. 10,25 Several studies have reported an association between high vWF levels and the risk of ischemic stroke. 11,43,44 We found increased vWF levels, vWF activity, and vWF HMWMs in patients with acute stroke .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation